2012
DOI: 10.1007/s00508-012-0303-1
|View full text |Cite
|
Sign up to set email alerts
|

Positive end-expiratory pressure lung recruitment: comparison between lower inflection point and ultrasound assessment

Abstract: In this study, positive end-expiratory pressures for recruitment of subpleural consolidations followed by ultrasound always exceed the pressures measured with LIP. Respecting this, ultrasound method could be the guide for PEEP lung recruitment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 28 publications
0
21
0
1
Order By: Relevance
“…Among lung US studies in ARDS, correlations of lung US aeration patterns with the pressure‐volume curve as well as CT have been demonstrated . Dependent lung regions seem to be poorly recruitable; however, this process probably depends on the strategy aimed at “opening” these poorly aerated tissues, as well as lung morphologic characteristics, although the last point is controversial . Of note, positive lung US imaging changes may not have a linear correlation with the improvement in oxygenation, as shown by Haddam et al and Wang et al as well as in a study that interestingly showed worsening aeration measured by lung US after fluid loading in septic patients with ARDS, without an alteration in oxygenation .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among lung US studies in ARDS, correlations of lung US aeration patterns with the pressure‐volume curve as well as CT have been demonstrated . Dependent lung regions seem to be poorly recruitable; however, this process probably depends on the strategy aimed at “opening” these poorly aerated tissues, as well as lung morphologic characteristics, although the last point is controversial . Of note, positive lung US imaging changes may not have a linear correlation with the improvement in oxygenation, as shown by Haddam et al and Wang et al as well as in a study that interestingly showed worsening aeration measured by lung US after fluid loading in septic patients with ARDS, without an alteration in oxygenation .…”
Section: Discussionmentioning
confidence: 99%
“…Among lung US studies in ARDS, correlations of lung US aeration patterns with the pressure‐volume curve as well as CT have been demonstrated . Dependent lung regions seem to be poorly recruitable; however, this process probably depends on the strategy aimed at “opening” these poorly aerated tissues, as well as lung morphologic characteristics, although the last point is controversial .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LUS score-quantified aeration changes observed in patients with ventilator-associated pneumonia upon initiation of antimicrobial therapy showed a tight correlation with CT measurements of lung aeration [8]. When compared with the pressure-volume curve method of assessing PEEP-induced lung recruitment in acute lung injury (ALI)/ARDS, the same score was accurate in detecting significant increases in lung aeration [16, 17]. During a successful spontaneous breathing trial, aeration changes measured by LUS scores may accurately predict postextubation distress [18].…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent study showed that lung reaeration can be estimated accurately with bedside lung US. 7 Recently, Rode et al 8 proposed that lung US could guide lung recruitment by using PEEP, with improvement in lung consolidation as a sign of improved alveolar ventilation. Presently, there is no systematic USguided lung recruitment protocol available for clinical use.…”
mentioning
confidence: 99%